Uxua Esteban - Design of an active a 5-bit digitally programmable phase shifter for hybrid antenna beamformers - Esteban, Uxua (Jornada de Jóvenes Investigadores del I3A, 2022)
Design of an active a 5-bit digitally programmable phase shifter for hybrid antenna beamformers